A CLINICAL STUDY ON GUNJATAILA AND TILATAILA SHIROABHYANGA IN THE MANAGEMENT OF DARUNAKA (AYUSHDHARA, 2017)
Background: Dandruff is an irritative disease of the scalp in which shedding of dead tissue from the scalp with itching sensation is the cardinal feature. It can be correlated to Darunaka. The cardinal symptoms of the disease Darunaka are Kandu (Itching), Keshachyuti (falling of hair), Swapa (abnormalities of touch sensation), Rookshata (roughness or dryness of the skin) and Twaksphutana (breaking or cracking of the skin). Yogaratnakara has mentioned the application of Gunjataila (i.e., Gunja, Bhringaraj, Tilataila) in the treatment of Darunaka. In the current dermatological practice there is no effective modern remedy for dandruff. Hence the present study is undertaken to find effective and safe alternative to conventional topical anti-dandruff agents. Objectives: To compare the effects of Shiroabhyanga with Gunjataila and Tila Taila in the management Darunaka. Materials and methods: This study was Randomized, open labelled, non-controlled, comparative clinical study. In Group A, Gujataila shiroabhyanga and in Group-B Tilataila Shiroabhyanga was done for thirty days, daily once in the morning, after the completion of treatment, all the patients were advised to attend the O.P.D for two months at regular interval of fifteen days for the follow up study to assess the post effects of treatment. Results: Group A showed complete remission in 30%, marked improvement in 30%, moderate 30% and 10% mild relief. In patients of Group B only 30% moderate relief and 10% mild relief from the Darunaka is noticed and 60% of the patients found no relief. Conclusion: Gunjataila shiroabhyanga has higher significant effect in pacifying the symptoms of Darunaka and marked reduction in clinical symptoms was well appreciated within one month duration. There was no topical and systemic adverse drug effects noted at the end of the study.